System Immersion in Virtual Reality-Based Rehabilitation of Motor Function in Older Adults: A Systematic Review and Meta-Analysis - Høeg, Emil Rosenlund; Povlsen, Tina Myung; Bruun-Pedersen, Jon Ram; Lange, Belinda; Nilsson, Niels Christian; Haugaard, Kristian Birkemose; Faber, Sune Mølgård; Hansen, Søren Willer; Kimby, Charlotte Kira; Serafin, Stefania (Frontiers in Virtual Reality, 2021)
Background: As the elderly population continues to grow, so does the demand for new and innovative solutions to tackle age-related chronic diseases and disabilities. Virtual Reality (VR) has been explored as a novel therapeutic tool for numerous health-related applications. Although findings frequently favours VR, methodological shortcomings prevent clinical recommendations. Moreover, the term 'VR' is frequently used ambiguously to describe e.g. video games; the distinction remains vague between immersive VR (IVR) systems and non-immersive VR (NVR). With no distinct demarcation, results of outcome measures are often pooled in meta-analyses, without accounting for the immersiveness of the system. Objective: This systematic review focused on virtual reality-based rehabilitation of older adults (+60) in motor rehabilitation programs. The review aims to retrospectively classify previous studies according to the level of immersion, in order to get an overview of the ambiguity-phenomenon, and to utilize meta-analyses and subgroup analyses to evaluate the comparative efficacy of system immersion in VR-based rehabilitation. Methods: Following PRISMA guidelines, we conducted a systematic search for randomized controlled trials, describing virtual rehabilitation or video games interventions for older adults (+60). Main outcomes were pain, motivation, mobility, balance and adverse events. Results: We identified 15 studies which included 743 patients. Only 3 studies utilized IVR. The rest used various NVR-equipment ranging from commercial products (e.g. Nintendo Wii), to bespoke systems that combine tracking devices, software and displays. A random effects meta-analysis of 10 studies analyzed outcome measures of mobility, balance and pain. Protocols and dosage varied widely, but outcome results were in favour of immersive and non-immersive interventions, however, dropout rates and adverse events were mostly in favour of the control. Conclusions: We initialize a call-for-action, to distinguish between types of VR-technology and propose a taxonomy of virtual rehabilitation systems based on our findings. Most interventions use NVR-systems, which have demonstrably lower cybersickness-symptoms than IVR-systems. Therefore, RCT adverse events may be under-reported. An increased demand for IVR-systems highlight this challenge. Care should be given, when applying the results of existing NVR tools to new IVR-technologies. Future studies should provide more detail about their interventions, and future reviews should differentiate between NVR and IVR.